The Murman Coast and the Northern Dvina Delta as English and Dutch Commercial Destinations in the 16th and 17th Centuries - Veluwenkamp, J.W. (ARCTIC, 1995)
In the sixteenth and seventeenth centuries, the Murman coast trade and the Northern Dvina trade were two clearly distinct branches of Western European commerce. The Murman coast trade involved the commerce with the regional economy of the Kola Peninsula, and the Northern Dvina trade coincided with the transit trade with the Russian interior. In the 1550s, the English established commercial relations with interior Russia via the mouth of the Northern Dvina, mainly exchanging woolen cloth and metals for north and central Russian forestry and agriculture products. In the 1570s, the Dutch followed suit, and by the second decade of the seventeenth century, they had squeezed the English almost completely out of the Russian market. The Northern Dvina trade became a major line of Dutch business, involving the transit trade with interior Russia, the exchange of the products of the north and central Russian forestry and agriculture for gold and silver money and a wide range of military stores and luxury goods. In the 1560s, the Dutch developed commercial relations with the Murman coast, exchanging locally produced exports like cod, salmon, furs and train oil for locally used imports like woolen cloth, tinware, salt, pepper, and wine. In addition, from the early 1570s, the Dutch used Kola as an alternative to the Northern Dvina mouth as a port for the transit trade with interior Russia; but they did so only until about 1585, when the tsar directed all foreign trade of interior Russia to proceed via the newly founded port of Archangel on the Northern Dvina. After that, Kola only remained an international commercial port for the local economy of the Murman coast. The Dutch continued to trade with the Murman coast on a very small scale throughout the seventeenth century, but Archangel was by far their main commercial destination in the Barents Sea area.Key words: Northern Dvina, Archangel, Murman coast, Kola, Russian trade, Dutch trade, English trade, commercial relations Au XVIe et XVIIe siècle, les échanges de la côte ...